Adhesive capsulitis of the shoulder, its relationship to diabetes mellitus, and the need for effective treatment (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Abstract not availableJ Bangladesh Coll Phys Surg 2024; 42: 221-222